Implementasi Manajemen Kurikulum 2013 dan Gaya Kepemimpinan Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan - Sujana, Dana; Zohriyah, Anis; Fauzi, Anis (Penerbit Widina, Widina Media Utama, 2021)
AbstractThis study aims to find out how the implementation of management curriculum 2013 and the leadership style of school principals improves the quality of education.This research is a type of qualitative research, with a field research approach. Data was collected by observation and interviews (primary) and data that came from various written/literary sources in the form of books, journals, magazines, and so on. (secondary). The data analysis used is descriptive data analysis by checking the validity of the data by using the triangulation technique.The results of the study revealed that the implementation of Management Curriculum 2013 was able to improve the quality of education. This is evidenced by the existence of a positive response from two directions in teaching and learning activities, the shift to student-centered learning. In addition, improving the quality of education is also supported by the leadership style of the school principal. This is evidenced by the acceptance of the concept initiated by the school principal, the skills to build and establish good relationships and the technical skills of the principal in managing and empowering all elements of the school can be implemented.